Los valores de las matrículas y la deserción universitaria en colombia (2020)
This study analyzes the effect of changes in the values of university tuition on dropout. Information on students between 2010 and 2016 is used, as well as the reconstructed enrollment values based on information from the Ministry of Education and the country's private universities. Estimating duration models, it is found that a 100% increase in the enrollment price index increases dropout by 6 percentage points, with differential effects for the different socioeconomic strata and for those who receive ICETEX credits and those who do not. The results indicate that the effect of the change in the value of tuition is greater for the most socioeconomically vulnerable students.